PENGARUH KINERJA KEUANGAN PERBANKAN BERDASARKAN ANALISIS CAMELS TERHADAP HARGA SAHAM DENGAN CSR SEBAGAI VARIABEL INTERVENING - Sulhan, Muhammad; Halimah, Dewi Nur (IQTISHODUNA, 2013)
" CAMELS method, as a standart of Bank of Indonesia to asses bank health, is employed to ratebanking health. Moreover, companies is eager to implement CSR program as a hidden way to attract publicattention. This study aims to identify and analyze the direct influence of financial ratios such as CAR, KAP,NPM, ROA, ROA and LDR on CSR and the direct influence of CAR ratio; KAP, NPM, ROA, BOPO, LDR andCSR on stock prices; and indirect influence of CAR, KAP, NPM, ROA, ROA and LDR ratios to the stock pricewith CSR as an intervening variable. The population in this study are 29 banks which has go public in theIndonesia Stock Exchange and the sample in this study are 10 banking companies. The results of the studywith 5% level of significance shows that 76.4% information contained in the data can be explained by themodel. While the diversity of the remaining 23.6% is explained by other variables. The result of partial assayshows that only ROA and LDR which have significant influence on CSR. In contrast, CAR, KAP, NPM, ROAand LDR have no significant influence on CSR. The partial influence of CAMELS on stock prices only CARand KAP which have no significant influence on the go public company’s stock price. While NPM, ROA,ROA, LDR and CSR have significant influence on the stock prices. And for the indirect influence, only ROAand LDR which have indirect influence on stock prices through CSR.